Computer-Assisted Solution of The DBF Equation Using the HCM for Flow through a Rectangular Porous Channel Bounded by Differentially Heated Horizontal Plate’s Demonstration Using Mayavi - S. B., Dr. Ashoka (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The system of non-linear algebraic equations arising from the application of the central difference approximation to the fully developed Darcy-Brinkman-Forchheimer flow equation is solved using the continuation method based on the Runge-Kutta45 order method. The fully-developed non-linear flow through a rectangular channel is considered and the influence of the Brinkman, Reynolds and Darcy numbers, the step size and variable viscosity parameter on the numerical results is investigated. Keywords: Brinkman, Reynolds , Darcy , Forchheimer, Runge-Kutta45, Mayavi